Effect of prices on marketing behavior of farmers - a distributed lag model approach - R.VIJAYA KUMARI, B.SOWJANYA, D.V. SUBBA RAO and (The Journal of Research, PJTSAU, 2017)
Present study was undertaken in the year 2011-12 in Nalgonda district of Andhra Pradesh to study the determinant of net income of farmers and effect of lagged prices on arrivals and current prices. Samples of 15 farmers were selected for collecting primary data. Secondary data includes prices and arrivals collected from Suryapet Agricultural Market Committee.Multiple linear regression analysis and autoregressive distributed lag models were used to analyze the data. In multiple linear regression analysis the coefficient of multiple determination was 97. Area, expenses on production material and expenses on marketing services were found significantly influencing the income of the farmers by Rs. 26704, Rs. 0.96 and Rs.0.22 respectively. Autoregressive distributed lag models for factors effecting arrivals, the coefficient of multiple determination showed that 83 percent of variation was explained by the variables in the model. Current prices and lagged prices Pt-1 (one month lag) were found significantly influencing the arrivals of paddy by 0.374 and 1.339 quintal. Similarly, Autoregressive distributed lag models for factors effecting current arrivals, the coefficient of multiple determination showed that 86 percent of variation was explained by the variables in the model. Lagged prices Pt-1 (one month lag), Pt-2 (two months lag) were found significantly influencing the current price of the paddy. The current prices of the farmer would have been more by Rs. 0.525 and 0.430 if the lagged prices (Pt-1 and Pt-2) were higher by one rupee.